BUDGET TRANSPARENCY, PUBLIC ACCOUNTABILITY, AND INTERNAL CONTROL IN LOCAL GOVERNMENT FINANCIAL MANAGEMENT: EVIDENCE FROM ACEH - Mukhtaruddin; Muhammad Azril (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2026)
This study aims to explore and gain an in-depth understanding of how budget transparency, public accountability, and internal control systems are enacted in the financial management practices of local governments in Aceh Province, and how these three aspects relate to local financial management performance. Sound local financial governance is a key prerequisite for achieving good governance, particularly in a region with special autonomy status such as Aceh. This study employs a qualitative approach with a descriptive case study design. Informants were selected through purposive and snowball sampling, comprising financial management officials, financial administration officers, internal government supervisory apparatus, and civil society actors involved in budget oversight across several regencies/cities in Aceh. Data were collected through in-depth interviews, non-participant observation, and documentation review, then analyzed using the interactive model of Miles, Huberman, and Saldana, comprising data reduction, data display, and conclusion drawing/verification. Data trustworthiness was established through source and method triangulation and member checking. The (illustrative) findings indicate that budget transparency is enacted through the openness of budget documents, yet still faces accessibility barriers for laypeople; public accountability is upheld through formal reporting mechanisms but remains limited in its responsiveness to public input; and the effectiveness of the internal control system is highly dependent on the commitment of unit leadership. Together, these three aspects form an interrelated pattern of local financial management that cannot be understood in isolation. This study offers rich contextual understanding to inform policy formulation for strengthening local financial governance in Aceh.